Controllable resonant type converter development for capacitor charging loads - Volkov, I.V.; Podolnyi, S.V. (Технічна електродинаміка, 2017)
The paper investigates various controlling options for the selected resonant converter topology, which is optimized for capacitor charging systems. Several of the controlling algorithms were studied in depth, and one of them was practically verified. There are two major advantages about the system: full/partial soft-switching mode what allows to use higher switching without the system efficiency drop; controllable energy flow from the input to the output, without any additional sophisticated parts.